Use of internet technologies in information and education enviroment in universities - Zhumagulova, S.К.; Sadanova, B.М.; Seidahmаtov, M.D. (Publ.KarSU, 2017)
This article describes the impact of the development of information technology on the learning process, the characteristics of the Internet educational resources were carried out. The analysis of trends in the use of modern information technologies in libraries was conducted. A wide range of services offered in Kazakhstan libraries of national importance is provided. The process of informatization of education in Kazakhstan with the introduction of computer technology in educational activities is reviewed. The use of information resources in the educational process enhances the effectiveness of the learning process, optimizes performance of trainees. Concept of internet technologies is introduced and its types such as WWW service, email and mailing lists, various search engines, ICQ, chats, html forums, guest book, teleconference, ftp servers and so on are examined. Also relevance of the use of information tools in education process, which accorfing to study results contributes to an improvement in an effectiveness of study process and optimization of activities of students, is demonstrated.
Жоғарғы оқу орынының ақпараттық білім беру ортасында интернет-технологияларды қолдану
Использование интернет-технологий в информационно-образовательной среде вуза
Keywords: development; website; internet; electronic textbooks; programming languages; technologies; educational institution; system; information; electronic resource